Physicochemical quality of artisanal oils produced in Ouagadougou: case of four small companies of cottonseed oils and crude groundnut oils taken in the markets - Souleymane, ZIO; Aly, SAVADOGO; Laurencia Toulsoumdé, SONGRE-OUATTARA; Francois, TAPSOBA; Henri Nestor, BASSOLE Imael; Cheikna, ZONGO; Flibert, NIKIEMA; Yves, TRAORE (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Artisanal oils dominate in the diet of the Burkinabe population.Among the food products, artisanal oils represent important sources of potential health risks. The objective of this study is to evaluate the quality of artisanal oils produced in Ouagadougou. A total of 30 samples of cottonseed oil and groundnut oil were collected on the sites of production and markets of Ouagadougou. The physicochemical parameters (refractive index, acid value, peroxide value, iodine value, saponification value, residual soap content, water and volatile materials content, Î²-carotene content, sterols and mineral oil) were determined by standard methods. The physicochemical parameters determined the case of non-compliance observed in the iodine and saponification values. The cottonseed oil showed 88.58 Â± 11.86 g of iodine / 100 g. This average is below the codex alimentarusstandard value. Sterols were detected in all samples. However no sample of oil showed traces of mineral oils. The averages of the physicochemical parameters according the type of oil presented significant variations (p Ë‚ 0.05)exceptedthose of the iodine value, the residual soap content, the water and volatile materials content. The overall analysis of the different results showed a general conformity with the Codex permissibility level for named vegetable oils. This compliance allows concluding that the quality of artisanal oils from Ouagadougou is quite good. It appears from this study that local producers have a mastery of the manufacturing process. But obtaining high quality of artisanal oil requires more strict application of good hygiene and manufacturing practices.